Application of Ice Breaking and Interactive Quizziz to Improve Student Learning Quality: Community Service Program at IPIEMS Surabaya Junior High School - Fauziyah, Farichatul; Alfani, Mukhammad (AMK : Abdi Masyarakat UIKA, 2024)
This article discusses the application of ice-breaking techniques and the interactive learning platform Quizizz to improve the quality of student learning at IPIEMS Junior High School Surabaya, Indonesia. In the digital era, innovative teaching methods are crucial, as traditional methods often do not meet the needs of diverse students. Ice-breaking activities are proven to increase student motivation and engagement, while Quizizz offers an interactive and fun learning experience, which encourages a deeper understanding of the material. This study aims to evaluate the impact of these methods on motivation, comprehension, and overall learning quality, with a blended approach involving surveys and interviews. The results showed a significant increase in student motivation and engagement after the implementation of these techniques. In addition, the ice-breaking activity created a more relaxed classroom atmosphere, encouraging active participation and reducing boredom, while Quizizz provided immediate feedback that supported critical thinking and a deeper understanding of the material taught. Overall, both methods proved effective in making the learning process more dynamic and interactive, ultimately contributing to improving the quality of education in the digital age.